The Effectiveness Analysis of Distance Learning by Optimizing the Use of Information Technology - Dede Ridho Firdaus; Budi Harto; Handy Ferdiansyah (Yayasan Gema Bina Nusantara, 2023)
In this study, the IS Success Model is used to analyze data on the use of information technology for distance learning during a pandemic in schools in order to determine the factors that influence the application of e-learning in remote learning systems. This study employed a quantitative approach to identify the elements that influence the effectiveness of using technology in distance learning activities. Data collection and data analysis procedure is needed for this research because this research uses quantitative approach to the problem. With respect to the research approach, researchers use methods, analytical techniques, and tools appropriate to the approach quantitatively to get precise results. The research has been successful in examining how information technology is employed in distance learning activities using the Delone and McLean models. As a result, it is possible to make the following conclusions: Google Classroom is the second most widely used program for use in remote learning activities after Zoom. Users' happiness with the usage of apps is influenced by information quality, service quality, user characteristics, and system use in this study.